2007
DOI: 10.1111/j.1601-6343.2007.00405.x
|View full text |Cite
|
Sign up to set email alerts
|

Change in maximum occlusal force in association with maxillofacial growth

Abstract: Maximum occlusal force tended to increase with age. There was a gender difference in the maximum occlusal force at all age groups, values being larger in the males. In the males, the maximum occlusal force continued to increase until their 20s, while in the females, this increase almost terminated at the age of 17.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
50
0
7

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(66 citation statements)
references
References 18 publications
9
50
0
7
Order By: Relevance
“…A similar correlation is not found in the control group. The increase in age in the test-group patients by 1 year, results in an increase of the maximum bite force on the left side on average by 19.6 N, and on the right side on average by 24 N. In the case of the average masticatory forces on the left side such increase is 17.3 N, and on the right side -20.5 N. Usui et al [18] showed in their work the increase in the value of masticatory forces with age. According to Bakke [2], bite force increases with age to about 12 years of age, then maintains at a similar level to 40-50 years of age, and then decreases.…”
Section: Discussionmentioning
confidence: 93%
“…A similar correlation is not found in the control group. The increase in age in the test-group patients by 1 year, results in an increase of the maximum bite force on the left side on average by 19.6 N, and on the right side on average by 24 N. In the case of the average masticatory forces on the left side such increase is 17.3 N, and on the right side -20.5 N. Usui et al [18] showed in their work the increase in the value of masticatory forces with age. According to Bakke [2], bite force increases with age to about 12 years of age, then maintains at a similar level to 40-50 years of age, and then decreases.…”
Section: Discussionmentioning
confidence: 93%
“…It has been suggested that bite force reflected the geometry of the lever system of the mandible (27). Greater mechanical advantage and relatively stronger bite forces are associated with more anteriorly inclined mandible, smaller anterior facial heights, greater posterior face height as well as a smaller gonial angle (16,24,26,28). In accordance with these results, in the present study, the healthy individuals showed negative correlation between bite force and anterior total face height, lower anterior face height, gonial angle and mandibular plane angle.…”
Section: Discussionmentioning
confidence: 99%
“…Usui et al (16) studied the correlation between maximum bite force and mandibular plane angle in most age groups and noted an important relationship between the maximum bite force of various skeletal types and face shape, which was not considered in the present study. Future studies should thus include a larger sample and different face shapes, to ensure more precise results.…”
Section: Discussionmentioning
confidence: 74%